Survival of Spinal Metastasis Disease based on Immunohistochemistry Subtype of Breast Cancer: A Systematic Review and Meta-analysis - Hadisaputra, Ivan Hugo; Mahadewa, Tjokorda Gde Bagus; Mardhika, Putu Eka (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Breast cancer is categorized as a slow-growth tumor in the spinal metastases disease (SMD) scoring system. Based on immunohistochemistry, breast cancer has four subtypes: Luminal A (LumA), luminal B (LumB), human epidermal growth factor 2 (Her-2) type, and triple-negative breast cancer (TNBC). TNBC has the poorest prognosis. AIM: This study aimed to describe the survival time of breast cancer with SMD based on immunohistochemistry subtypes through systematic review and meta-analysis. METHODS: This is a systematic review and meta-analysis study. This study used electronic articles published in PubMed and CENTRAL online database. We used keywords ([breast] AND [cancer] AND [spine] AND [metastasis]) to find eligible studies. Articles included were full-text studies in English. Survival time as the outcome was pooled according to the immunohistochemistry subtype of breast cancer. Statistical analysis was performed using software Stata. RESULTS: Five articles met our inclusion and exclusion criteria. LumA, LumB, Her-2 type, and TNBC have a survival time of 32.84 months, 35.20 months, 60.8 months, and 14.27 months, respectively. CONCLUSION: TNBC has the lowest survival time in the pooled analysis. We proposed TNBC be categorized as a moderate growth primary tumor.